Simulation and Experiments of Hypervelocity Impact in Containers with Fluid and Granular Fillings - Matura, Pascal; Heilig, Georg; Lueck, Martin; Sauer, Martin (Procedia engineering, 2015)
This paper presents both experiments and associated numerical simulations of hypervelocity impacts (approx. 3000m/s) of spherical aluminum projectiles onto hollow aluminum cylinders with either water or sand filling, which serve as representative filling substances for fluid and powdery materials, respectively. High-speed video technique is used to monitor the impact process. The paper mainly focuses on the following two subjects: (a) A direct comparison of failure and fracture of the container shell and the associated release of the filling depending on its type in both experiment and simulation. (b) With the above mentioned cases as reference examples, the applicability and efficiency of different numerical methods is investigated, such as Langrangian discretizations with Finite Element (FE)/Smoothed Particle Hydrodynamics (SPH) coupling, a coupled adaptive FE/SPH discretization and a coupled Euler/Lagrange method. The influence of the different simulation methods in terms of container failure representation and ejecta cloud properties is investigated and compared with the experimental results.